A regional survey of current practices on destination marketing organizations’ Facebook Pages: the case of EU and U.S. - Stankov, Uglješa; Jovanović, Tamara; Pavluković, Vanja; Kalinić, Časlav; Drakulić-Kovačević, Nataša; Cimbaljević, Marija (Geographica Pannonica, 2018)
Constantly changing nature of social network sites creates the need for continuous process of onlinebenchmarking for identifying practices used by other parties. Facebook as the most used SNS still playsan increasingly important role as a marketing channel for destination marketing organizations (DMO).This paper explores basic characteristics of the official DMO Facebook Pages in order to quantify andpresent those characteristics in a regional context on the case of two travel markets (EU countries andU.S. states). The results show inconsistent practices in the EU and the USA. When comparing those twomarkets most similarities in practices are present in general usage of Facebook Pages, while indicativedifferences are recorded in terms of Page popularity, some posts’ characteristics and most evidently inusers’ engagement. Understanding the Facebook usage practice under the regional spotlight can helpDMOs and other service providers to evaluate their activities and if necessary to harmonize it to regional usage practice.
Keywords: European Union; United States of America; destination marketing organization; social network sites; Facebook